2022
DOI: 10.3389/fonc.2022.1022123
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant immunotherapy combined with chemotherapy significantly improved patients’ overall survival when compared with neoadjuvant chemotherapy in non-small cell lung cancer: A cohort study

Abstract: BackgroundProgrammed death-1 (PD-1)/programmed death ligand-1 (PD-L1) inhibitors displayed considerable advantages in neoadjuvant therapy of non-small cell lung cancer (NSCLC), but the specific application of neoadjuvant immunotherapy has not been well determined, and the long-term prognostic data of neoadjuvant immunochemotherapy combined with surgical resection of NSCLC remains limited. In this study, we intended to assess the efficacy of the neoadjuvant therapy of the PD-1 inhibitor and long-term prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
(50 reference statements)
2
3
0
Order By: Relevance
“…In a retrospective study, patients who achieved pCR had better OS and DFS [34] and this conclusion was also been proved in Checkmate 816 [20]. However in our study, pCR was not associated with better EFS, and NADIM confirmed the same conclusion [30].…”
Section: Discussionsupporting
confidence: 78%
“…In a retrospective study, patients who achieved pCR had better OS and DFS [34] and this conclusion was also been proved in Checkmate 816 [20]. However in our study, pCR was not associated with better EFS, and NADIM confirmed the same conclusion [30].…”
Section: Discussionsupporting
confidence: 78%
“…Recently, Zhang et al 18 conducted a retrospective study among stage IB-IIIB lung cancer patients and found that VATS achieved comparable efficacy to open surgery, with shorter ICU stays for patients, indicating the safety, efficacy, and feasibility of VATS as a surgical strategy for patients after immunotherapy. 19 Our results similarly demonstrated that patients who underwent MIS after immunotherapy had equally favorable prognoses to those who underwent thoracotomy. MIS not only maintained a clear field of vision for lymph node dissection but also offered advantages such as shorter operation times, less intraoperative blood loss, and fewer postoperative complications.…”
Section: Discussionsupporting
confidence: 74%
“…While several articles have mentioned the use of MIS in the surgical treatment of lung cancer patients after immunotherapy, 16,17 reports directly comparing MIS with thoracotomy have been limited. Recently, Zhang et al 18 conducted a retrospective study among stage IB–IIIB lung cancer patients and found that VATS achieved comparable efficacy to open surgery, with shorter ICU stays for patients, indicating the safety, efficacy, and feasibility of VATS as a surgical strategy for patients after immunotherapy 19 . Our results similarly demonstrated that patients who underwent MIS after immunotherapy had equally favorable prognoses to those who underwent thoracotomy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In resectable NSCLC, major pathologic response (MPR) after neoadjuvant chemoimmunotherapy or chemotherapy was associated with better EFS and OS [23,24]. In our study, e cacy of induction therapy achieve PR patients had better PFS and OS than SD patients.…”
Section: Discussionmentioning
confidence: 54%